Cat and mouse in a haunted house. (New York : Scholastic, 2004)
Mouse journalist Geronimo Stilton enters an abandoned mansion after getting lost in a frightening forest and finds that his refuge is haunted by cats.
Translated from the Italian.
"Geronimo Stilton."
3.4
3-6
3-6
410
Keywords: Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Haunted houses -- Juvenile fiction; Journalists -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Fiction; Mice -- Fiction; Haunted houses -- Fiction; Journalists -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Stilton, Geronimo (Fictional character) -- Fiction; Mice -- Fiction; Haunted houses -- Fiction; Journalists -- Fiction; Humorous fiction; Adventure fiction; Humorous fiction; Adventure fiction